Religious Perspectives on Abortion and a Secular Response - Stephens, Moira (Journal of religion and health, 2010)
This paper concerns the medical, religious, and social discourse around abortion. The primary goal of this paper is to better understand how seven of the world's major religious traditions (Roman Catholic, Lutheran, Jewish, Islamic, Buddhist, Confucian, and Hindu) address abortion in the clinic'. We do not aim to critique these commentaries but to draw out some of the themes that resonate through the commentaries and place these within complex social contexts. We consider the intersection of ontology and morality; the construction of women's selfhood; the integration of religious beliefs and practices in a secular world. We suggest that for many women, religious doctrine may be balanced with secular logic as both are important and inextricably linked determinants of decision making about the termination of pregnancy.